2013
DOI: 10.2298/jsc130520057g
|View full text |Cite
|
Sign up to set email alerts
|

A test of Clar aromatic sextet theory

Abstract: The Clar aromatic sextet theory predicts that the intensity of cyclic conjugation in chevron-type benzenoid hydrocarbons monotonically decreases along the central chain. This regularity has been tested by means of several independent theoretical methods (by the energy effects of the respective sixmembered rings, as well as by their HOMA, NICS, and SCI values, calculated at the B3LYP/6-311G(d,p) level of DFT theory). Our results show that the predictions of Clar theory are correct only for the first few members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Theoretical investigations have shown that Clar's theory should find limitations when going to large systems, that were not objects of consideration by Clar himself . The present investigation adds a new warning to the applicability of Clar's theory.…”
Section: Resultsmentioning
confidence: 59%
“…Theoretical investigations have shown that Clar's theory should find limitations when going to large systems, that were not objects of consideration by Clar himself . The present investigation adds a new warning to the applicability of Clar's theory.…”
Section: Resultsmentioning
confidence: 59%
“…Several examples documenting disagreements between the actual π-electron structure of benzenoid hydrocarbons, and what is predicted on the basis of the Clar aromatic sextet theory, have been reported in the past [13,14,[24][25][26][27]. The cases studied in this work offer a further indication of such disagreements.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 58%
“…Eventually, much effort has been done to provide a quantitative and theoretically founded re-formulation of Clar's model (see the recent works [16][17][18][19][20][21][22][23][24] and the references cited therein). In our earlier studies [13,14,[24][25][26][27], examples of benzenoid hydrocarbons were found in which the predictions of Clar theory were violated. However, the benzenoid systems in these examples contained fixed single and double carbon-carbon bonds, and thus it could be argued that Clar theory was not strictly applicable to them.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] In particular, on the perimeter of a benzenoid system, one distinguishes features called fissures, bays, coves, and fjords, 13,14,19,20 cf. [14][15][16][17][18] In particular, on the perimeter of a benzenoid system, one distinguishes features called fissures, bays, coves, and fjords, 13,14,19,20 cf.…”
Section: Structural Features Of Altan-benzenoidsmentioning
confidence: 99%
“…As a direct consequence of this, some π-electron 1520 GUTMAN properties of annulenes 6,[22][23][24] are preserved also in altan-benzenoids. 15,[25][26][27] Another characteristic feature of the π-electron configuration of (4k)annulenes is the existence of a pair of non-bonding molecular orbitals (NBMOs). Of their properties, the most important may be that cyclic conjugation has a significant destabilizing energy effect.…”
Section: π-Electron Properties Of Altan-benzenoidsmentioning
confidence: 99%